Characterization of Zn-Substituted Nano-Sized CoAl2O4 Powder Synthesized by Egg-White Method - Al-Angari1, Y.M.; Gabal1, M.A.; Al-Agel2, F.A. (Asian Journal of Chemistry, 2014)
In the present study, a simple and environmental friendly egg-white was utilized for the preparation of nano-crystalline Co0.5Zn0.5Al2O4. The decomposition process of the precursor was followed through TG measurement. XRD, FT-IR and TEM techniques to characterize the produced aluminate. The obtained XRD pattern indicates the formation of single-phase cubic structure. FT-IR exhibited two characteristic bands of aluminate structure. TEM image showed cubic agglomerated particles with an average size of about 20 nm. Ac-conductivity measurements indicates the semiconducting properties of the obtained aluminate with room temperature conductivity of 3.4 × 10-4 W-1 cm-1.